Competitive gerrymandering and the popular vote - Felix Bierbrauer; Mattias Polborn (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Gerrymandering undermines representative democracy by creating many uncompetitive legislative districts, and generating the very real possibility that a party that wins a clear majority of the popular vote does not win a majority of districts. We present a new approach to the determination of electoral districts, taking a design perspective. Specifically, we develop a redistricting game between two parties who both seek an advantage in upcoming elections, and show that we can achieve two desirable properties: First, the overall election outcome corresponds to the popular vote. Second, most districts are competitive.
Keywords: D72; C72; 330; Gerrymandering; legislative elections; redistricting